Sosialisasi Dampak Lingkungan Terhadap Penularan TB dan Filariasis di Negeri Hatuhenu Kecamatan Amahai Kabupaten Maluku Tengah - Souisa, Gracia Victoria; Vauza, Zukiflin P (Universitas Nusantara PGRI Kediri, 2018)
Negeri Hatuhenu, Amahai Sub-district, Central Maluku District, based on interviews with health officials and the government of the country, have various health problems such as clean and healthy living behavior, environmental sanitation problems that have an impact on the emergence of environment-based diseases such as tuberculosis, filariasis and malaria. To solve the above health problems, the lecturers and students of the Public Health Study Program in collaboration with health officials, the government of Hawahenu and Haatenu are conducting counseling on